2002
DOI: 10.1128/mcb.22.24.8409-8414.2002
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Developmental Defects Derived from Impaired Recruitment of ASC-2 to Nuclear Receptors in Mice: Implication for Posterior Lenticonus with Cataract

Abstract: ASC-2, a recently isolated transcriptional coactivator molecule, stimulates transactivation by multiple transcription factors, including nuclear receptors. We generated a potent dominant negative fragment of ASC-2, encompassing the N-terminal LXXLL motif that binds a broad range of nuclear receptors. This fragment, termed DN1, specifically inhibited endogenous ASC-2 from binding these receptors in vivo, whereas DN1/m, in which the LXXLL motif was mutated to LXXAA to abolish the receptor interactions, was inert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 25 publications
2
49
1
Order By: Relevance
“…Transfection and luciferase assays were performed in triplicate as described in ref. 41, and the results were normalized to the LacZ expression. Similar results were obtained in 2 independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Transfection and luciferase assays were performed in triplicate as described in ref. 41, and the results were normalized to the LacZ expression. Similar results were obtained in 2 independent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…ASC-2, also termed AIB3, TRBP, RAP250, NRC and PRIP ( Fig. 2A), is a co-activator interacting with histone H3-lysine 4-specific methyltransferase and its function is also required in vivo for αA-, γD-and γF-crystallins (Kim et al, 2002). Some of the DNAbinding factors, e.g.…”
Section: Role Of Pax6 In Tissue-restricted and Tissue-specific Gene Ementioning
confidence: 99%
“…Interestingly, ASC-2 null lenses exhibit reduced expression of the αA-but not αB-crystallin (see Table 1). ASC-2 is a transcriptional coactivator of nuclear receptors, AP-1 and other transcription factors that function in the lens (Kim et al, 2002). Additional studies of the mouse αA-crystallin locus including its promoter are required to fully understand regulatory mechanisms that account for its temporal and spatial regulation and links to the fiber-cell differentiation signals.…”
mentioning
confidence: 99%
“…This enzyme is a component of a large multisubunit complex ASCOM, a coactivator complex of nuclear receptors. The complex includes activating signal cointegrator 2 (ASC-2) with a pair of LXXLL motifs (Plevin et al, 2005) (see Table 1) that was earlier shown to participate in regulation of mouse lens development and crystallin gene expression (Kim et al, 2002).…”
Section: Histone Modifications and Histone-modifying Enzymes-postransmentioning
confidence: 99%